Characterization of self-assembled silver nanoparticle ink based on nanoemulsion method - Donghao Hu; Kazuyoshi Ogawa; Mikio Kajiyama; Toshiharu Enomae (Royal Society Open Science, 2020)
A well-dispersed self-assembled silver nanoparticles (AgNPs) ink with high purity was synthesized via AgNO3 emulsion prepared by blending an AgNO3 aqueous solution and a liquid paraffin solution of both polyoxyethylene (20) sorbitan monooleate (Tween 80) and sorbitan monooleate (Span 80). The ink remained as an emulsion at low temperatures; however, it produced AgNPs after sintering at about 60°C and showed a high stability at nanoscale sizes (with diameters ranging 8.6–13.4 nm) and a high conductivity. During the whole procedure, Tween 80 acted as a surfactant, reductant and stabilizer. Presumably, Tween 80 underwent an autoxidation process, where a free radical of an α-carbon of ether oxygen was formed by hydrogen abstraction. The mean diameter of emulsion droplets could be reduced by decreasing water content and increasing the ratio of surfactant and concentration of AgNO3 aqueous solution. Consequently, the thermogravimetric analysis and X-ray diffraction result clarified the purity of the produced Ag0. Dynamic light scattering and ultraviolet-visible spectroscopy clarified that an increased concentration of AgNO3 decreased the particle size.